Comparative Analysis of Implementing Innovation Development Vector by Hotel Enterprises in Pandemic - A. N. Ivanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The current economic situation in hotel business functioning exerts serious impact on its development in conditions of innovation paradigm. Innovation of work is a key link in the development of hotel enterprises in today’s world. The author grounds topicality of using innovation in the work of hotel enterprises, studies the dynamics of innovation activity level at hotel enterprises in Moscow, investigates the structure of expenses on innovation projects in the work of hotel enterprises and makes a comparative analysis of the rate of innovation activity of hotel enterprises in Moscow and some European capitals. In research materials the author on the basis of retrospective statistics underlines a serious impact of pandemic on the level of innovation at hotels. To make comparative analysis of the rate of innovation activity at hotel enterprises in Moscow the author recommends using the coefficient of advancing /retarding, which is formed on the basis of comparing the index of expense growth on implementing innovation projects and the index of efficiency indicator growth of hotel enterprises.